Synthesis and Biological Evaluation of Novel Heterocyclic Imines Linked Coumarin- Thiazole Hybrids as Anticancer Agents - Goud, Nerella S.; Ghouse, Mahammad S.; Vishnu, Jatoth; Pranay, Jakkula; Alvala, Ravi; Talla, Venu; Qureshi, Insaf A.; Alvala, Mallika (Anti-Cancer Agents in Medicinal Chemistry, 2019)
Background: Human Galectin-1, a protein of lectin family showing affinity towards β-galactosides has emerged as a critical regulator of tumor progression and metastasis, by modulating diverse biological events including homotypic cell aggregation, migration, apoptosis, angiogenesis and immune escape. Therefore, galectin-1 inhibitors might represent novel therapeutic agents for cancer. Methods: A new series of heterocyclic imines linked coumarin-thiazole hybrids (6a-6r) was synthesized and evaluated for its cytotoxic potential against a panel of six human cancer cell lines namely, lung (A549), prostate (DU-145), breast (MCF-7 & MDA-MB-231), colon (HCT-15 & HT-29) using MTT assay. Characteristic apoptotic assays like DAPI staining, cell cycle, annexin V and Mitochondrial membrane potential studies were performed for the most active compound. Furthermore, Gal-1 inhibition was confirmed by ELISA and fluorescence spectroscopy. Results: Among all, compound 6g 3-(2-(2-(pyridin-2-ylmethylene) hydrazineyl) thiazol-4-yl)-2H-chromen-2- one exhibited promising growth inhibition against HCT-15 colorectal cancer cells with an IC50 value of 1.28 ± 0.14 μM. The characteristic apoptotic morphological features like chromatin condensation, membrane blebbing and apoptotic body formation were clearly observed with compound 6g on HCT-15 cells using DAPI staining studies. Further, annexin V-FITC/PI assay confirmed effective early apoptosis induction by treatment with compound 6g. Loss of mitochondrial membrane potential and enhanced ROS generation were confirmed with JC-1 and DCFDA staining method, respectively by treatment with compound 6g, suggesting a possible mechanism for inducing apoptosis. Moreover, flow cytometric analysis revealed that compound 6g blocked G0/G1 phase of the cell cycle in a dose-dependent manner. Compound 6g effectively reduced the levels of Gal-1 protein in a dose-dependent manner. The binding constant (Ka) of 6g with Gal-1 was calculated from the intercept value which was observed as 1.9 x 107 M-1 by Fluorescence spectroscopy. Molecular docking studies showed strong interactions of compound 6g with Gal-1 protein. Conclusion: Our studies demonstrate the anticancer potential and Gal-1 inhibition of heterocyclic imines linked coumarin-thiazole hybrids.
Keywords: thiazole